(untitled) (World Bulletin of Public Health, 2024)
Molecular-biochemical parameters of the endothelial system of the lungs during experimental modeling of abdominal sepsis showed an ambiguous picture of the changes occurring, which were of a phase nature and depended on the timing of the development of the pathological process